Clinical performance evaluation of five commercial IgM tests for diagnostic of Zika virus infection - Didye Ruiz; Carlos M Torres; Mayling Alvarez; Pedro A Martinez; Naifi Calzada; Lianna M Garcia; Maria G Guzman (Open Journal of Tropical Medicine - Peertechz Publications, 2020)
Background: Zika Virus (ZIKV) is an emerging mosquito-transmitted flavivirus currently causing large epidemics and represents a global public health. Most ZIKV infections in humans are asymptomatic or mild with self-limiting clinical manifestations. Certainty, an available and sustainable surveillance for risk individual groups to ZIKV infection it is necessary and serological methods offer a good alternative. Objective: To evaluate the clinical performance of five commercially serologic assays for the detection of anti ZIKV IgM. Study design: A sera panel of 200 samples, including 100 positive and 100 negative serum to ZIKV infection, all characterized by molecular and serological standard diagnostic assays, was used in the evaluation. Three ELISA (Euroimmun, DiaPro and IBL), one immunochromatographic (Artron) and an immunoblot (Mikrogen) assays were evaluated. Results: Evaluated assays showed acceptable specificities (>80%) and variable sensitivities. The highest sensitivity was found for DiaPro-ELISA (87.8 %), following by IBL-MAC-ELISA (64.9%) and Mikrogen-Immunoblot (52.0%). Both Euroimmun (15.6%) and Artron (18.0 %) showed a poor sensitivity. The strongest agreement with the molecular reference was found by DiaPro-ELISA (kappa: 0.87), for IBL and Mikrogen was moderate (kappa: 0.56 and 0.45) and poor for Euroimmune and Artron (kappa: 0.16 and 0.02). DiaPro and Euroimmun showed a similar ZIKV IgM detection rate in DENV immune and naïve cases. Cross-reactivity for negative specimens was lower with the exception of Artron-RT assay. Conclusions: Between the five evaluated assays, DiaPro-ELISA provided the best-assessed parameters for serum samples collected between days 5 to 7 of onset of symptoms.